Market Reaction On Changes In Corporate's Name On The Indonesia Stock Exchange - Candra Astra Terenggana, Heriyanto, (Jurnal Manajemen, 2019)
The market reaction on changes in corporate's name on the Indonesia Stock Exchange. This study tried to investigate empirically market reaction over the announcement of corporate name changes of companies on the Indonesia Stock Exchange. The market reaction is measured by using abnormal return with a single index model approach. The database of corporate name change announcements on the Indonesia Stock Exchange has obtained from an annual fact book report. The sample of this study consists of the companies that make a name change from 2005 to 2017. Hypothesis test uses one sample t-test. This research's result proves that there was a positive and significant market reaction to the corporate name change announcement. Moreover, This researchÃ¢â‚¬â„¢s result shows that there was a positive and significant reaction on the corporate name change announcement which is included on major change while at the corporate name change announcement which included on minor change there was no significant market reaction. Ã‚Â Ã‚Â